Oxidative Addition of Haloheteroarenes to Palladium(0): Concerted versus SNAr‐Type Mechanism. Issue 21 (8th April 2015) - Maes, Bert U. W.; Verbeeck, Stefan; Verhelst, Tom; Ekomié, Audrey; von Wolff, Niklas; Lefèvre, Guillaume; Mitchell, Emily A.; Jutand, Anny
Abstract The kinetics of the oxidative additions of haloheteroarenes HetX (X=I, Br, Cl) to [Pd0(PPh3)2] (generated from [Pd0(PPh3)4]) have been investigated in THF and DMF and the rate constants have been determined. In contrast to the generally accepted concerted mechanism, Hammett plots obtained for substituted 2‐halopyridines and solvent effects reveal a reaction mechanism dependent on the halide X of HetX: an unprecedented SNAr‐type mechanism for X=Br or Cl and a classical concerted mechanism for X=I. These results are supported by DFT studies.